CODE MIXING IN SUHAY SALIM BEAUTY VLOGGER - AINI, IRHAYATUL (LANGUAGE HORIZON, 2019)
AbstractPhenomenon called code mixing currently becomes a well-known event in Indonesia. Indonesians tend to combine two languages or more in every utterances or sentence and upload it in social media. The reason for this may come from their surrounding environment (external factors) or their desire (internal factors). This study aims to determine how Suhay Salim, a popular beauty vlogger on YouTube, mixes her languages between Bahasa Indonesia and English in each of her videos. Analysis of the video demonstrated that there are three types of code mixing and five reasons influencing Suhay Salim?s code mixing found in her video. The results indicate that Insertion becomes the dominant type of code mixing because word is the smallest unit that can be inserted into a given structure easily. It also indicates that the most occurring reason influencing Suhay Salim is Low Frequency Words where Bahasa Indonesia word is harder to remember, less popular and has unstable sense/meaning while English word is easier to remember, more popular and has stable sense/meaning.Keywords: code mixing, social media, video, beauty vlogger.